Estimating Company Value of PT HOLCIM Indonesia, TBK - Nursalim, Kayom Mukti; Noveria, Ana (Journal of Business and Management, 2014)
Abstract- The author performed a valuation of PT Holcim Indonesia Tbk. PT Holcim Indonesia Tbk is a member of Holcim Group who holds majority and minority interests in more than 70 countries on all continents. Valuation of a company can help determine the worth of an asset by the process of linking risk and return, valuation can be applied to expect streams of benefits from bonds, stocks, income properties, and so on. Different methods were utilized in the research to estimate the value of the company. First is Discounted Cash Flow method, second is Asset Based Method, and the third is Market Approach. Three scenarios are used in the discounted cash flow method which was optimistic scenario, most likely scenario, and pessimistic scenario to generate a more actual result and more realistically illustrated the company’s condition. Results of the company’s valuation may differ for each method due to different focus and theory. Analysis of optimal capital structure of the Company is applied to find the optimal proportion of debt, equity, and the capital of the company, after finding the optimal proportion it is used by the author to know how the company could enhance its value. Theoretical stock price is also generated from the calculated company value. The theoretical stock price generated will be compared with the market value by the author to determine the status of the company’s share price and determine whether it is undervalued or overvalued, by PT Holcim Indonesia Tbk share price, the author made a series of analysis on how PT Holcim Indonesia Tbk could enhance its value, how the company can use it as a strategy to get a higher valuation, funding options, and investment choice. Keywords: Company Valuation, Discounted Cash Flow Method, Optimal Capital Structure